Pengaruh Mutasi Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas Kesehatan Provinsi Gorontalo - Regina Triyulianti Aulia Eraku; Rosman Ilato; Roy Hasiru (State University of Gorontalo, 2023)
The objective of this research was to find out to what extent the effect of job mutations on the performance of civil servants at the Department of Health of Gorontalo Province. Moreover, The research method used was a quantitative research method where the data collection techniques were observation, questionnaires, and documentation, and the data analysis was done through simple regression analysis. The research finding depicted that the statistical hypothesis was accepted, and there was an effect of job mutations on the performance of civil servants at the Department of Health of Gorontalo Province. The effect of job mutations on the performance of civil servants was 68.4%, while the remaining 31.6% was affected by other variables that were not examined in this research.